2021
DOI: 10.1155/2021/6959322
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Reduced FEF25-75% and a Positive Methacholine Challenge Test in Adults with Nonobstructive Baseline Spirometry

Abstract: Rationale. FEF25-75% is routinely reported on spirometry and is thought to be a marker of small airway obstruction. It is reduced in children with asthma, but its significance in adults and especially those without asthma diagnosis remains unclear. Objective. To clarify whether in adults with a nonobstructive spirometry a reduced FEF25-75% is associated with a positive methacholine challenge test (MCT). Methods. Data was collected for all the patients who had a MCT done between April 2014 and January 2020 but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In addition, it has been recently demonstrated that reduced FEF 25–75 was predictive for positive methacholine challenge test in subjects with normal FEV 1 and FEV 1 /FVC values. In other words, an impaired FEF 25–75 value (< 65% of predicted) suggested the presence of bronchial hyperreactivity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been recently demonstrated that reduced FEF 25–75 was predictive for positive methacholine challenge test in subjects with normal FEV 1 and FEV 1 /FVC values. In other words, an impaired FEF 25–75 value (< 65% of predicted) suggested the presence of bronchial hyperreactivity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These conditions include obstructive lung diseases, like asthma, methacholine airway responsiveness, ambient ozone, torquetenovirus, anthracofibrosis, trawler fuel exhaust, ataxiatelangiectasia (AT), left ventricular hypertrophy in patients with morbid obesity, and BMI. [33][34][35][36][37][38][39][40][41] The relationship between this ratio and restrictive lung disease has not been directly studied in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…These conditions include obstructive lung diseases, like asthma, methacholine airway responsiveness, ambient ozone, torquetenovirus, anthracofibrosis, trawler fuel exhaust, ataxiatelangiectasia (AT), left ventricular hypertrophy in patients with morbid obesity, and BMI. [33][34][35][36][37][38][39][40][41] The relationship between this ratio and restrictive lung disease has not been directly studied in previous studies.…”
Section: Discussionmentioning
confidence: 99%